Impuesto a los consumos especiales y su incidencia en el consumo del cigarrillo en el Ecuador. Período 2007 – 2013 - Pico Aguilar, Ana Lucía (2015)
The present research shows that the implementation of the Special Consumption Tax to cigarettes, has failed to reduce the consumption of this well, becoming a regressive tax revenues, affecting people with lower income. In developing the current tax laws and revised its evolution since its inception, the purpose for which it was created the tax and the impact that had on consumption. the existing database of tax collection was used to see its evolution and compare them with the levels of production and importation of cigarettes in the country. The price elasticity of demand of the cigarette, which is considered an inelastic good for the results obtained was determined and finally an analysis of the socio-economic effects of cigarette smoking in Ecuador was conducted.